2017
DOI: 10.2174/1874285801711010283
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungi Increase the Phenolic Compounds Concentration in the Bark of the Stem of Libidibia Ferrea in Field Conditions

Abstract: Background: Libidibia ferrea is a species particular to the caatinga presenting medicinal properties for containing bioactive compounds. The use of Arbuscular Mycorrhizal Fungi (AMF) can increase the production of biomolecules in the legume leaves; however, no light has been shed on the role of symbiosis in maximizing metabolites production in the bark of L. ferrea stem.Objective:The aim was to select AMF that are efficient at increasing the production of phenolic compounds with medicinal properties in the bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 36 publications
1
20
0
1
Order By: Relevance
“…For instance, AMF treatments caused an increase in phenolic compounds content of lettuce [ 53 , 66 ], and in the antioxidant capacity of sweet basil [ 67 ]. Moreover, the flavonoids of some wild plants, such as Libidibia ferrea , were found to be accumulated by mycorrhizal association [ 68 ]. Similarly, eCO 2 induced the accumulation of some phenolic compounds in birch [ 69 ], and Zingiber officinale [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, AMF treatments caused an increase in phenolic compounds content of lettuce [ 53 , 66 ], and in the antioxidant capacity of sweet basil [ 67 ]. Moreover, the flavonoids of some wild plants, such as Libidibia ferrea , were found to be accumulated by mycorrhizal association [ 68 ]. Similarly, eCO 2 induced the accumulation of some phenolic compounds in birch [ 69 ], and Zingiber officinale [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several scenarios have been proposed to explain the induction of secondary metabolites in response to AMF associations and eCO 2 . It was found that AMF could affect secondary metabolites through improved photosynthesis and mineral content of the host plants, activation of pathways involved in synthesis of secondary metabolites, or higher expression of some genes related to secondary metabolism [ 68 ]. On the other hand, the eCO 2 -induced changes in plant secondary metabolism have been attributed to either excess amount of non-structural carbohydrates, resulting in an increment in carbon-based secondary metabolites [ 9 , 37 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been carried out to investigate the effects of AMF inoculation on the concentration of secondary metabolites compounds. Flavonoids concentration was shown to have increased in the bark of Libidibia ferrea after being inoculated with Claroideoglomus etunicatum and Gigaspora albida; similarly, the concentration of total tannins was shown to be higher when inoculated with Acaulospora longula compared to the non-inoculated control plants [28]. Arbuscular mycorrhizal fungi species can also have different effects in the host; for instance, Copetta et al [29] showed that Glomus mossea increased the concentration of alpha-terpineol-an essential oil from Ocimum basilicum-compared to Gigaspora margarita, Gigaspora rosea and non-inoculated control plants.…”
Section: Introductionmentioning
confidence: 92%
“…In another study carried out under nature conditions, Zeng et al (2014) found that Glomus versiforme improved the quality of citrus fruits by increasing the ratio of sugar to acid, and the amounts of vitamin C, flavonoids and minerals. Another woody plant beneficed by mycorrhization in field is Libidibia ferrea , a tree with medicinal properties whose bark accumulated higher amount of flavonoids and tannins when associated with AMF ( dos Santos et al, 2017 ). Mycorrhizal fungi also improved the antioxidant potential of leaves from sweet basil, an aromatic plant widely used for medicinal and cooking purposes ( Hristozkova et al, 2017 ).…”
Section: Impact Of Amf On the Quality Of Crops And Fruits Undergoing mentioning
confidence: 99%